Co2 Biofixation And Carbohydrate Biosynthesis By Locally Isolated Acidophilic Microalgae For Biobutanol Production Through Simultaneous Saccharification And Fermentation - Tan, Kean Meng (2023)
Butanol is a common chemical that used as an additive for automotive fuel. Among the production methods, the biobutanol synthesised through acetone-butanol-ethanol (ABE) fermentation process. The ABE fermentation using microalgae biomass that contains high carbohydrate with less lignin, which is suitable to be biobutanol feedstock. The potential of microalgae for biological CO2 biosequestration, making them value-added compared to other bioresources. In addition, the promising single-step saccharification and fermentation (SSF) process during ABE fermentation, has opened up a novel ground for advancement in economic biobutanol production. Based on this study, a total of two native acidophilic microalgae were successfully isolated and were identified as Coccomyxa dispar and Scenedesmus parvus strains. The C. dispar and S. parvus exhibited highest in terms of biomass productivity, carbohydrate productivity, and CO2 biofixation when cultivated under the elevated condition. Apart from that, the carbohydrate-related genes and proteins were also been investigated in this study. Based on the transcriptomic analysis, the results showed that a significant upregulated of carbohydrate-related genes such as AGB, SS, ISA, AGPase, ME, G6PD, Accc, RuBC, and CA that involved in C. dispar, while PGM, AGB, SS, AGPase, ME, DGAT, RuBC, and CA involved in S. parvus